Olivia - Falconer, Ian, 1959- (New York : Atheneum Books for Young Readers, 2000)
Whether at home getting ready for the day, enjoying the beach, or at bedtime, Olivia is a feisty pig who has too much energy for her own good.
"An Anne Schwartz book.".
Caldecott Medal/Honor.
School Library Journal starred.
Wilson's Children.
Book Links (A.L.A.), April 2003.
Booklist starred, August 2000.
Keywords: Behavior -- Fiction; Pigs -- Fiction; Human behavior -- Fiction; Pigs -- Fiction